Investigating the Relationship between Hba1c Level and Dental Caries in Type 2 Diabetic Patients - Firouzi , Ali; Rajabbi, Mehrdad; Kiany, Farin (Galen Medical Journal, 2024)
Background: Diabetes Mellitus is among the most frequent enduring metabolic disorders in the broad populace and leads to many complications, including tooth decay. In this study, the relationship between HbA1c level and dental caries has been investigated to be a step towards increasing awareness and improving the health status and quality of life of diabetics. Materials and Methods: This cross-sectional study was carried out on 20 type 2 diabetic who referred to dental clinic of shiraz university of medical sciences between 2022 and 2023 and were separated into two categories of managed diabetes (HbA1c under 7%) and uncontrolled (HbA1c above 7%). The desired data were obtained through a questionnaire containing demographic information, clinical examination (DMFT (Decayed, Missing, Filled Teeth) index), oral hygiene, and carbohydrate consumption. Results: The average DMFT index is greater in individuals with unmanaged diabetes compared to those with Controlled Diabetes, though not statistically significant (P=0.137). However, as BMI increases, so does the DMFT index (P=0.035). There is no notable correlation between HbA1c levels and dental caries (P=0.2). Oral hygiene practices did not significantly affect the DMFT index (P=0.943). Carbohydrate intake per day did not impact the DMFT (P=0.34). Higher education levels were associated with a decrease in DMFT, though not statistically significant (P=0.172). Conclusion: Considering the higher rate of dental caries in individuals with uncontrolled diabetes, it is necessary to inform these patients about more oral and dental hygiene and blood sugar control.